Podnikatelský plán s podporou strukturálních fondů EU - Boltižiar, Víťazoslav (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Diplomová práce se zabývá problematikou realizace podnikatelského plánu za podpory strukturálních fondů Evropské Unie. V první části se zabývá shrnutím teoretických východisek pro práci. V druhé části poté samotným vytvořením podnikatelského plánu. Tato část obsahuje podnikatelský záměr, analýzu konkurence a trhu, potenciálních zákazníků, studii proveditelnosti a možnosti podpory ze strany EU. Výstupem práce je ucelený projekt.

This master’s thesis approaches the problematic of the creation of a business plan, financed with the support from European Union Structural Funds. The first part brings the review of theoretical knowledge and the second part elaborates the detailed conception of a business plan. This section contains a business idea, market analysis and analysis of competition and potential customers. Furthermore, feasibility study is constructed and available support from the EU structural funds described. The result of this work is an integrated project.
Business Plan with European Union Structural Funds Support
Keywords: Podnikatelský plán; Evropská unie; dotace; financování projektu; strukturální fondy; Business plan; European Union; funding; project financing; structural funds